Inovasi Penggunaan Laboratorium Keperawatan Pada Masa Pandemi Covid 19 - Siti Fatimah; Putra Adi Syani; Pontni Pontni (LPPM STIKes Panca Bhakti Bandar Lampung, 2023)
This study aims to find out what innovations were carried out by the nursing laboratory during the covid19 pandemic and also to determine the level of effectiveness in using the use of the nursing laboratory during the covid19 pandemic. This study uses a qualitative approach with interview and observation techniques to find out innovations in using of nursing laboratories at UIN Jakarta. The results of this study indicate that the innovations carried out by the nursing laboratory of UIN Jakarta during the covid19 pandemic were with the help of information technology, that is by implementing e-learning (video tutorials, tool redemonstrations). The application of this innovation succeeded in overcoming the limitations faced during the pandemic even though the effectiveness of this innovation it was not optimal, this was reflected in the decrease in the average value of practicum and student satisfaction compared to before the pandemic where students could practice directly in the lab. With this research, many of the lecturers suggested that innovations that should be applied to nursing practicums were Patient Simulations Scenarios and Augmented Reality.